Effect of conformation, flexibility and intramolecular interaction on ion selectivity of calix[4]arene-based anion sensors: experimental and computational studies. Issue 8 (3rd August 2017) - Maity, Debdeep; Bhatt, Madhuri; Desai, Mittal L.; Suresh, E.; Si, Mrinal Kanti; Boricha, Vinod P.; Ganguly, Bishwajit; Paul, Parimal
Abstract: A number of calix[4]arene-based molecules were designed incorporating amide moiety with variation in conformation, rigidity at the binding sites and steric crowding at the upper rim to investigate the anion sensing property of this series of ionophores. These compounds were synthesised and characterised, molecular structures of two of the compounds were established by single-crystal X-ray study. Anion binding property of these ionophores, investigated with the aid of 1 H NMR and UV–vis spectroscopy, revealed that three (1–3 ) out of four ionophores strongly interact with F −, in addition, ionophore2 interacts with CN − and, ionophore3 interacts with CH3 COO − and and ionophore4 does not interact with any anions. NMR titration was carried out to determine binding constant with strongly interacting anions. Crystal structure analysis revealed that strong intramolecular interaction in4 prevented the anions to interact with the N–H protons of the amide moiety. Interestingly, 2 with F − and CN − exhibits sharp colour change in acetonitrile–chloroform. Apparently, conformation of the calix moiety, flexibility of the binding sites and intramolecular H-bonding played critical role towards determination of selectivity. Computational study was performed to investigate the interaction site(s) and also to corroborate some of the experimental results. Abstract : Anion binding study of functionalised calix[4]arenes revealed that conformation, flexibility and intramolecular interaction in calix moiety play critical role to determine ion selectivity. One of the receptors performs as sensitive colorimetric sensor for F − and CN −, computational study also corroborates most of the experimental results.